Immunotherapy versus chemotherapy as first-line treatment for advanced urothelial cancer: A systematic review and meta-analysis. (March 2022) - Martini, Alberto; Raggi, Daniele; Fallara, Giuseppe; Nocera, Luigi; Schultz, Julianne G.; Belladelli, Federico; Marandino, Laura; Salonia, Andrea; Briganti, Alberto; Montorsi, Francesco; Powles, Thomas; Necchi, Andrea
Highlights: In this Meta-analysis we aimed to compare the effectiveness of single-agent immune-oncology (IO) compounds versus platinum-based chemotherapy as first-line treatment for advanced urothelial carcinoma (aUC). In published studies on IO versus chemotherapy there is "early crossing" of the Kaplan-Meier (KM) curves. This almost invariably coincides with the violation of the proportional hazard assumption. In this scenario, the hazard ratios obtained from the Cox regression do not reflect the real pattern of the event free survival. To overcome this issue, we relied on the difference in restricted mean survival time (Δ RMST) for OS comparison. We included data from 2, 068 individuals from 3 phase III trials. An algorithm obtained OS from Kaplan-Meier curves. There was no OS benefit for patients treated with immune checkpoint inhibition as first line compared to chemotherapy in the overall population, among cisplatin ineligible patients and in the PD-L1 high population. Abstract: Background: Pembrolizumab and atezolizumab have recently been approved for the first-line treatment of patients with advanced urothelial carcinoma (aUC) who are not eligible for cisplatin-based chemotherapy and whose tumors have high PD-L1 expression; however, the use of these immunotherapeutic agents relative to standard of care chemotherapy has ongoing concerns. The aim of this present study is to compare the effectiveness of single-agent immune-oncology (IO) compounds versus platinum-based chemotherapy in the first-line setting of aUC. Methods: A comprehensive search for phase III trials on IO versus chemotherapy was conducted in PubMed, EMBASE, Web of Science, and Scopus databases from 01/2016 to 05/2021. An algorithm to obtain survival data from published Kaplan-Meier curves was used to reconstruct overall survival (OS) data. After demonstrating violation of the proportional hazard assumption, we used the difference in restricted mean survival time (Δ RMST) to compare OS. Results: OS data from 2, 068 individuals from 3 phase III trials investigating the role of IO vs chemotherapy were reconciled. Overall, patients receiving IO [n = 1, 013 (49%)] or chemotherapy [n = 1, 055 (51%)] had similar OS with a 24-month Δ RMST of −0.4 (95% CI: −1.1, 0.4; p = 0.2) months. In the cisplatin-ineligible population, patients receiving IO [n = 509 (49%)] or chemotherapy [n = 530 (51%)] had similar OS with a 24-month Δ RMST of 0.1 (95% CI: −0.9, 1.2; p = 0.7) months. In the cisplatin-ineligible population with PD-L1-high tumors, patients receiving IO [n = 226 (50%)] or chemotherapy [n = 226 (50%)] had similar OS with a 24-month Δ RMST of 1.1 (95% CI: −0.5, 2.7; p = 0.1) months. Conclusion: We found no OS benefit for patients treated with first-line immune checkpoint inhibition compared to chemotherapy among the overall population, cisplatin-ineligible patients, and PD-L1-high patients.